About the relation of inequality and poverty with crime in Mexico - Calderón, Sully; Valero Gil, Jorge Noel (2012)
This article studies the relation between crime and inequality and between crime and poverty in Mexico using reported crime data from 1963 municipalities from the years 2000 and 2005. It uses two measures of crime, property and violent crime, and two measures of inequality, one for income and one for education; it also distinguishes between the concepts of mean income and poverty (marginality). The results show a positive relation between crime and inequality and poverty in cross section regressions. When we control for heterogeneity, the relation between violent crime and poverty is lost and the regressions lose much of their explanatory power. This means that although there is a strong relation between crime and variables such as inequality, poverty, migration and others, once a higher level of crime is reached, perhaps governments cannot use these variables to decrease it